2012
DOI: 10.2320/matertrans.m2012150
|View full text |Cite
|
Sign up to set email alerts
|

Sintered Behaviors and Electrical Properties of Cr50Cu50 Alloy Targets via Vacuum Sintering and HIP Treatments

Abstract: Powder metallurgy is the conventional process for the production of CrCu alloys. Enhanced vacuum sintering techniques and the use of HIP processes can be applied to obtain higher densities and decreased porosity in the sintered parts. In this study, the optimal sintering process of Cr50Cu50 alloy targets is 1270°C for 1 h; a high density and low electrical resistivity of the alloy targets is obtained. The experimental results also indicate that the relative density of the Cr50Cu50 vacuum sintering targets can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In this research, hot-press sintering was effective in providing the driving force of the sintering mechanism and helping the atomic diffusion due to external pressure (12 MPa). Therefore, the Cr50Cu50 alloys could achieve a good sintering effect at a relatively low temperature (1050°C) as compared with our previous vacuum sintering study 7) (the optimal vacuum sintering temperature of Cr50Cu50 alloy is 1270°C). When the hot-press sintering temperature was increased to 1100°C, the relative density and apparent porosity showed no obvious change.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…In this research, hot-press sintering was effective in providing the driving force of the sintering mechanism and helping the atomic diffusion due to external pressure (12 MPa). Therefore, the Cr50Cu50 alloys could achieve a good sintering effect at a relatively low temperature (1050°C) as compared with our previous vacuum sintering study 7) (the optimal vacuum sintering temperature of Cr50Cu50 alloy is 1270°C). When the hot-press sintering temperature was increased to 1100°C, the relative density and apparent porosity showed no obvious change.…”
Section: Resultsmentioning
confidence: 68%
“…The major diffractions appeared in the Cr (110), (200) and Cu (111), (200), (220) planes, respectively. Due to the crystal structure dependence on the XRD diffraction intensity, 6,7) it was reasonable to suggest that all Cr50Cu50 alloys possessed a good crystalline property after hot-press sintering under the different temperatures. Significantly, the two thermodynamically immiscible metals of chromium and copper produced no alloy phases after the hotpress sintering processes; only the pure chromium and copper peaks appeared in the XRD patterns, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has also proven the relationship of the relative density of Cr-based alloys to the electrical properties. 20) Increasing the relative density signi cantly improved the electrical properties of the Crbased alloys. Thus, it could be inferred that the higher relative density and lower porosity of the hot-press sintered Cr50Ni50 alloys led to the increase in the mean free path of the electrons, which improved the electrical performance.…”
Section: )mentioning
confidence: 99%
“…Our previous study indicated that when the sintering temperature increased, the relative density rapidly increased, and the apparent porosity clearly decreased [54,56]. Fig.…”
Section: Densities and Vickers Hardness Of The Resulting Micro-fluidimentioning
confidence: 95%
“…When the temperature was increased to 1200°C and then 1300°C, the surface roughness ratio of the WC-Co alloys was rapidly reduced. The surface roughness ratio appeared in the 1410°C sintering for 1 h; this result indicated that the sintering temperature was close to the liquid-phase sintering temperature [56]. Thus, the sintering temperature approached the liquid-phase sintering temperature for tungsten carbides, which would enhance the volume shrinkage ratio and lead to good sintering materials.…”
Section: Roughness Variation Of the Micro-specimensmentioning
confidence: 83%